JUDGE’S DECISION ON LEGALIZATION AND/OR LICENSING OF INTERFAITH MARRIAGES - Moh. Yusuf Bachtiyar; Hanif Nur Widhiyanti; Herman Suryokumoro (International Journal of Innovative Technologies in Social Science, 2022)
This study intends to explore and evaluate the wording of legality and licensing of interfaith weddings as mentioned in the Purwokerto District Court Decision No. 54/Pdt.P/2019/PN. Pwt. and the Surabaya District Court Decision No. 916/Pdt.P/2022/PN. Sby. In addition to studying and assessing the basis of the ratio decidendi used by courts to determine the legality of marriages between individuals of different religions, as required by law. This form of investigation is legal investigation. This investigation will employ the Statute Approach, Case Approach, and Conceptual Approach. The findings suggest that the conflict between the necessity of recording marriage events in state papers and the necessity of marital validity must end immediately. Article 2 paragraph (1) of the Marriage Law is extremely subjective, allowing for multiple interpretations, and at the level of implementation, these norms are very easily prepared, allowing them to be implemented and gain state legitimacy without requiring individuals to abandon their religion or original beliefs. The state must be present to defend the beliefs of its citizens, uphold its fundamental rights, and legitimize all legal activities conducted by its residents. Decision No. 68/PUU-XII/2014 of the Constitutional Court affirmed that religious law must be a factor in evaluating the validity or invalidity of marriage, including the invalidity of interfaith marriages. Consequently, the Constitutional Court’s Decision No. 68/PUU/XII/2014 has instructed and offered instructions for the right, fair, and scientific reading, understanding, and interpretation of Article 2 Paragraph (1) of Law No. 1 of 1974 in accordance with legal science.